Relationship between nutritional status and development of children aged 2-5 years in Iraonogaila village, Lahomi . district - Yusni Widayati Harefa; Jernihati Krisniat Harefa; Masri Yanti Jaya Hia (Institute of Computer Science (IOCS), 2022)
The most important phase in a child's growth and development is during the toddler years because that is the most vital time for parents to build the foundation for their baby's growth and development. Research purposes. This study aims to determine the relationship between nutritional status and the development of children aged 2-5 years in the village of Iraonogaila, Lahomi District. Research design. This research is an observational analytic using a cross sectional approach. Population. All families with toddlers aged 2-5 years in the village of Iraonogaila, Lahomi District. Sample. A total of 64 people using the Total population technique. Instrument. By using the Dacin and developmental pre-screening questionnaire. Data analysis. It was carried out in two stages, namely: univariate analysis and bivariate analysis. Research result. The results showed that the nutritional status was good with appropriate development as many as 39 people (60.9%), with doubtful development as many as 15 people (23.4%) and with deviant development as many as 3 people (4.7%). More nutritional status with appropriate development as many as 2 people (3.1%). Undernutrition status with dubious development was 1 person (1.6%) and with deviant development as many as 4 people (6.2%). Conclusion. There is a significant relationship between nutritional status and the development of children aged 2-5 years, namely <ɑ = (0.000 <0.05). Recommendation. It is recommended for parents to provide developmental stimulation to children and pay attention to good nutritional intake in children so that children do not experience developmental delays or deviations.